2014
DOI: 10.3233/jhd-130075
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Atrophy in R6/2 Mice – Altered Circulating Skeletal Muscle Markers and Gene Expression Profile Changes

Abstract: Background: In addition to classical neurological symptoms, Huntington's disease (HD) is complicated by peripheral pathology, including progressive skeletal muscle wasting, and common skeletal muscle gene expression changes have been shown in HD mice and human HD. Objective: To highlight possible mechanisms underlying muscle wasting in HD, we examined gene expression in pathways governing skeletal muscle contractility, skeletal myogenesis, skeletal muscle wasting, apoptosis and the NFκB signaling pathway in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 61 publications
3
18
0
Order By: Relevance
“…In general, it is believed that mitochondrial dysfunction and energy deficits underline HD pathology; for a review see [14]. Our results were in line with a previous study in the R6/2 mouse model that showed increased levels of circulating markers of muscle injury in the serum and a reduction of contractile transcripts [15]. It is interesting to compare these results to those found in cancer cachexia; animal models of urothelial carcinoma or Lewis lung carcinoma showed decreased respiratory chain activity [16] and a lower level of ATP [17], respectively, similarly to HD mouse models [11].…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…In general, it is believed that mitochondrial dysfunction and energy deficits underline HD pathology; for a review see [14]. Our results were in line with a previous study in the R6/2 mouse model that showed increased levels of circulating markers of muscle injury in the serum and a reduction of contractile transcripts [15]. It is interesting to compare these results to those found in cancer cachexia; animal models of urothelial carcinoma or Lewis lung carcinoma showed decreased respiratory chain activity [16] and a lower level of ATP [17], respectively, similarly to HD mouse models [11].…”
Section: Introductionsupporting
confidence: 90%
“…However, it is also possible that an intrinsic component of the HTT mutant gene product, expressed within muscle cells, might directly lead to pathogenic consequences. In addition, it has been shown that R6/2 mice had elevated levels of NFκB pathways that may be involved in muscle atrophy [15]. Similarly, increased levels of pro‐inflammatory cytokines like tumor necrosis factors (TNF) and interleukin 1 (IL‐1), caused by dysfunction of hypothalamic serotonergic neurons, have been implicated in cancer cachexia [26].…”
Section: Introductionmentioning
confidence: 99%
“…Altered gene expression in skeletal muscle has been shown to reflect HD progression 8 , including activation of apoptotic and NFκ-B pathway transcripts in R6/2 mice 26 . We therefore evaluated gene expression changes related to muscle damage and cachexia in gastrocnemius skeletal muscle, and the effects of 2 and 4 weeks of ghrelin treatment on these alterations.…”
Section: Resultsmentioning
confidence: 99%
“…HD myocytes have been shown to exhibit increased expression of genes encoding, for example, chaperones and heat shock proteins, and muscle-specific mRNAs have been shown to be altered 8 , 48 . The increased expression of genes involved in apoptosis and autophagy 25 , 26 suggests that these mechanisms may contribute to a catabolic phenotype and muscle wasting. In line with this, we here confirmed that R6/2 mouse skeletal muscle exhibits a catabolic gene expression profile.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the disparity between brain pathology and phenotype are likely to be complex. For example, there is considerable peripheral pathology in these mice [60][61][62][63][64][65], so the rapid deterioration in phenotype is unlikely to be due solely to brain dysfunction.…”
Section: Neurodegeneration In R6/2 Micementioning
confidence: 99%